Analisis Sentimen Ulasan Produk Suncreen Wardah Pada Marketplace Shopee Menggunakan Metode Naïve Bayes - Rambe, Nurhayati; Harahap, Syaiful Zuhri; Ritonga, Ali Akbar; Bangun, Budianto (Journal of Computer Science and Information System(JCoInS), 2025)
The development of the digital world and the popularity of online marketplaces such as Shopee have changed the way consumers interact and review products. Reviews of Wardah sunscreen products, which have an important role in skin health, are one of the most widely found. Understanding the sentiment of these reviews is crucial for manufacturers to improve product quality. Therefore, this study aims to analyze and classify consumer sentiment towards Wardah sunscreen products on Shopee. Using the Naïve Bayes classification method, the reviews will be categorized into positive, negative, and neutral sentiments to get an overall picture of the public perception of the product.